2015
DOI: 10.1186/s13054-015-0972-z
|View full text |Cite|
|
Sign up to set email alerts
|

Neutrophil CD64 expression as a diagnostic marker for sepsis in adult patients: a meta-analysis

Abstract: IntroductionNeutrophil CD64 (nCD64) expression appears to be a promising marker of bacterial infections. The aim of this meta-analysis was to assess the accuracy of nCD64 expression for the diagnosis of sepsis in critically ill adult patients.MethodsWe systematically searched PubMed, Embase, ISI Web of Knowledge, and the Cochrane Library for literature published between database inception and 19 May 2014, as well as reference lists of identified primary studies. Studies were included if they included assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 44 publications
(43 reference statements)
5
61
0
4
Order By: Relevance
“…Cluster of differentiation 64 (CD64, FcγRI) antigen is involved in neutrophil phagocytosis, oxidative burst and target killing [12] and has been promising in the early detection of bacterial infection [13-18]. Monocyte/macrophages are also key players in the innate immune response to infection.…”
Section: Introductionmentioning
confidence: 99%
“…Cluster of differentiation 64 (CD64, FcγRI) antigen is involved in neutrophil phagocytosis, oxidative burst and target killing [12] and has been promising in the early detection of bacterial infection [13-18]. Monocyte/macrophages are also key players in the innate immune response to infection.…”
Section: Introductionmentioning
confidence: 99%
“…A 2015 meta-analysis using adult studies sought to determine the relationship between nCD64 and the diagnosis of sepsis [85]. The AUC of the summary ROC curve was 0.95 with a Q* value of 0.89, and pooled specificity and sensitivity of 85% and 76% respectively [85].…”
Section: Biomarker Reviewmentioning
confidence: 99%
“…The AUC of the summary ROC curve was 0.95 with a Q* value of 0.89, and pooled specificity and sensitivity of 85% and 76% respectively [85]. A prior meta-analysis by Cid et al included studies performed on patients of all ages, and found the pooled sensitivity to be 79%, specificity 91%, and AUC 0.94 for nCD64 expression to predict bacterial infection [86].…”
Section: Biomarker Reviewmentioning
confidence: 99%
“…Proinflamatuvar sitokinler (IL-6, IL-1β, IFN-γ, TNF-α), antiinflamatuvar sitokinler (IL-4, IL-10, TGF-β), kemokinler (GRO-α, IL-8, IP-10, MIG), akut faz reaktanları (CRP, PCT, SAA, inter α inhibitör protein, LPS bağlayıcı protein), lökosit yüzey antijenleri (CD11b, CD64) ve diğer (mannoz bağlayıcı lektin, pro-adrenomedullin, pro-endotelin, pro-atrial natriüretik peptid gibi) belirteçlerin kullanımı önerilmektedir (34,35). Sepsis için ideal biyobelirteç özellikleri şu şekilde sıralanabilir:…”
Section: A Sitokinlerunclassified